THE UNSTABLE SIGN DŪD: A BARTHESIAN DOUBLE DECONSTRUCTION OF ANTHROPOCENTRIC AND ECOLOGICAL MYTHS IN “AL-DŪDAH” - Tafkur Bahril Wahid; Muhammad Azwar; Muhammad Syafi' Putra Prayoga (ALLAIS Journal of Arabic Language and Literature, 2026)
In Ḥasan ‘Abd al-Mawjūd’s short story “al-Dūdah”, a single Arabic word, dūd, carries meanings that contradict one another. The same word names a maggot, an earthworm, and a parasitic pinworm, and across the narrative it passes from disgust to a companion, a food, a pollutant, and at last a sovereign. This study asks how one unstable sign becomes the ground on which two opposed worldviews compete for authority. Using a qualitative-descriptive method and Roland Barthes’s tiered model of signification, it examines all sixteen occurrences of dūd and dūdah across denotation, connotation, and myth. At the denotative level, the sign is an unstable hypernym that stands, by metonymy, for organic nature in its cycle of decay. At the connotative level, it fragments across the characters and then converges again on that cycle. At the level of myth, the text sets the Myth of Anthropocentric Control against the Myth of Ecological Sovereignty. Both myths naturalize their claims through one shared mechanism and break against one shared material limit. The study offers double deconstruction, a method that reads two opposed myths with a single instrument and grants neither the status of settled truth.